Evolution of Algerian influence in African Jihadist movements. Issue 2 (3rd April 2022) - Wicks, Sammie; Weiss, Caleb
ABSTRACT: Algerian leadership was once instrumental in organising and fomenting jihad in North Africa and the Sahel. Alongside leadership decapitations, counter-terrorism crackdowns, and a 'Sahelian shift' following the influx of Sahelian members, Algerian influence has since significantly waned. Today, Algerian influence is mainly seen in cautionary tales against extremism and infighting. In contrast, few Algerian jihadists still play a role within the overall hierarchy of al-Qaeda's North African and Sahelian branches. As such, it is ultimately a new generation – a non-Algerian generation – that is leading the jihadist charge in northern Africa and the Sahel. However, although diminished, Algerian leadership remains persistently valuable to al-Qaeda's senior leadership due to their strategic utilitarian view.